Using Graphic Organizer as a Media in Students’ Writing Project - Anastasia Dewi Anggraeni; Helda Jolanda Pentury (Scope : Journal of English Language Teaching, 2018)
“Picture tells a thousand words“. It is important that teachers help the students organize their writing which they are learning to build and enhance their writing skill. Graphic organizer is a creative great media for comparing and contrasing text or story and can easily be applied to any kind of topic to help the students understand the differences between the texts or stories. Beside that aim, graphic organizer also helps the students to organize their writing skill and enhance their writing skill well. Graphic organizer is considered to enhance student’s writing skill, also expresses the students creativity by using the all kind of text, image and graphics, so the research employing observation and carried by descriptive research method. By implementing the strategy of using graphic organizer in students’s writing project, teacher will hopefully get the insight of using creative media to enhance students’ writing skill. Key words: graphic organizers; media, writing